Leishmaniose visceral canina no município de Uberlândia, Minas Gerais, outubro 2007 a fevereiro de 2008 - Borges, Gabriel Labeca Ferreira Nogueira (2008)
The aim of this research was to evaluate the hypothesis of Uberlândia presenting LVC in two areas that represent a potential risk of arrival and dissemination of LV in this city, as well as clarifying the role of the kennel APA (ANINAL PROTECTION AGENCY) and the homes localized at the Tenda dos Morenos and Buracão for the epidemiology of LV in the city. For that reason, a sectioned study was done in these places. At APA, a sampling activity was done with 85 dogs, which were photographed, identified, evaluated for visual inspection and submitted to blood drawings with filter paper at the tip of the ear for the making of RIFI ou ELISA at the LACEN of FUNED. In 25 of these animals it was also collected blood drawings samples, through puncture in the vessels of thoracic/pelvic members, for the realization of PCR of blood at the Molecular Biology Laboratory at UFU. The fifty five dogs in the homes of the Tenda dos Morenos and Buracão region were identified, evaluated by visual inspection and submitted to blood drawing sampling at the tip of the ear with filter paper and were sent to LACEN of FUNED from Belo Horizonte for the realization of the ELISA and RIFI tests. The animals reactive to some of these tests were re-tested with ELISA or RIFI and also with PCR of blood. In spite of the clinical findings which were very compatible to the LVC at the APA, no positive animals were found for the illness in the investigated regions. Thus, the moment regarding attention to health issues for LV in these regions is of primordial prevention and primary prevention, in order to avoid the formation of the bond parasite-reservatory-vetor. Therefore, the conjugation of this serum tests along with molecular tests has shown to be of great importance so the canine monitoring can be satisfactory.